Assessing the value of political science in the era of relevance and impact. Issue 4 (2nd October 2017) - Head, Brian W.
ABSTRACT: The political science profession, like other social sciences, is under pressure from many quarters to demonstrate its 'relevance'. This need arises primarily from requirements for universities to justify public investment in their teaching and research. Competition across the full range of science and humanities disciplines for public and private funding makes this an important challenge for all. This article reflects on how political scientists have seen the public value of their professional work. It concludes by suggesting some alternative ways of thinking about relevance, value and impact.